Financial frictions and wage inequality. (1st September 2020) - Pi, Jiancai; Fan, Yanwei
Abstract: This paper investigates how financial frictions affect skilled‐unskilled wage inequality. In both the cost constrained model and the quantity constrained model, we find that a decrease of financial frictions in the skilled (resp. unskilled) sector will increase (resp. decrease) wage inequality when there is a properly large elasticity of substitution between capital and skilled labor (resp. unskilled labor). In sum, the role of financial frictions is sector‐specific, which is largely neglected by the existing literature.